TWO SUBSTITUTIONS IN ONE SPECIAL NO HOMOGENEOUS VECUA EQUATION - Ilievski, Borko; Brsakoska, Slagjana; Sokoloski, Petar (Matematichki Bilten, 2007)
In this paper two theorems are proved and according to them the special no homogenous Vecua equation (6) is transformed to the basic Vecua equation (8).